Toll-Like Receptor 7 Enhances Rabies Virus-Induced Humoral Immunity by Facilitating the Formation of Germinal Centers - Luo, Zhaochen; Li, Yingying; Zhou, Ming; Lv, Lei; Wu, Qiong; Chen, Chen; Zhang, Yachun; Sui, Baokun; Tu, Changchun; Cui, Min; Chen, Huanchun; Fu, Zhen F.; et al. (Frontiers in Immunology, 2019)
Rabies virus (RABV) causes fatal encephalitis in mammals and poses a public health threat in many parts of the world. Vaccination remains the most effective means for prevention and control of rabies. Studies focusing on the mechanism of RABV immunogenicity are necessary for improvement of rabies vaccines. Toll-like receptor 7 (TLR7), an innate receptor sensing single-stranded viral RNA, is important for the induction of innate and adaptive immunity. Our studies revealed that the absence of TLR7 led to a lower antibody production in mice immunized with RABV. It is further found that TLR7 deficiency affected the recruitment of germinal center (GC) B cells and led to lessened GCs formation. Consistently, there was less plasma cells (PCs) and antibody secreting cells (ASC) in TLR7-/- mice than wild type (WT) mice, resulting in impaired production of RABV-neutralizing antibodies (VNA). TLR7 deficiency also impaired the generation of memory B cells (MBCs) and the induction of secondary immune responses. Moreover, TLR7 deficiency down-regulated the induction of some cytokines/chemokines, especially IFN-γ, resulting in a Th2-biased antibody production. Overall, our results suggest that TLR7 facilitates the induction of the humoral immunity in response to RABV.